2007
DOI: 10.1021/ja076797c
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Cyclopropanation of Enones with Dimethyloxosulfonium Methylide Promoted by a La−Li3−(Biphenyldiolate)3 + NaI Complex

Abstract: Catalytic asymmetric cyclopropanation of enones with dimethyloxosulfonium methylide using a La−Li3−(biphenyldiolate)3 + NaI complex is described. The present method is complementary to the previously reported catalytic enantioselective methods in terms of ylides used, and trans products were exclusively obtained in good yield (96−73%) and high enantioselectivity (99−84% ee). Use of biphenyldiol 1b-H2 and NaI additive was essential to achieve high enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(50 citation statements)
references
References 14 publications
0
50
0
Order By: Relevance
“…The molecular structure of 3 is quite similar to that of analogous La complex [36], in which the central Nd ion is bound to three chelating asymmetric guanidinates and coordinated to one THF molecule in a capped octahedron. The average Nd-N bond distance of 2.492(6) Å is in the range for the published analogues [7] and the C-N distances within the chelate rings (av. 1.345(5) Å) are consistent with partial double bond character.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The molecular structure of 3 is quite similar to that of analogous La complex [36], in which the central Nd ion is bound to three chelating asymmetric guanidinates and coordinated to one THF molecule in a capped octahedron. The average Nd-N bond distance of 2.492(6) Å is in the range for the published analogues [7] and the C-N distances within the chelate rings (av. 1.345(5) Å) are consistent with partial double bond character.…”
Section: Introductionmentioning
confidence: 81%
“…For example, the heterobimetallic binaphthoxide and phenoxide complexes of lanthanide and alkali metals have been explored to be versatile asymmetric catalysts in organic syntheses [1][2][3][4][5][6][7][8][9]. Various organometallic complexes of trivalent lanthanide and alkali metals [10][11][12][13][14][15][16][17], as well as the complexes of divalent lanthanide and sodium metals [18,19] have proven to be more effective catalysts in polymerization of nonpolar and polar monomers than their corresponding lanthanide complexes without alkali metals.…”
Section: Introductionmentioning
confidence: 99%
“…For the Corey-Chaykovsky cyclopropanation of enones and an R, -unsaturated N-acylpyrrole 13 as an ester surrogate, biphenyldiol 1-H 2 gave better enantioselectivity than BINOL (Scheme 3). 14,15 In cyclopropanation, a NaI additive also played a key role to improve enantioselectivity. Electrospray ionization mass spectrometry (ESI-MS) analysis, as well as control experiments, indicated that a partial alkali metal exchange occurred in situ to afford a La-Li 2 -Na-tris(biphenoxide 1) complex as the most reactive and enantioselective active species (Scheme 3).…”
Section: New Development In Remb Catalystsmentioning
confidence: 99%
“…Tamiflu (14) 26 is thought to be effective for protecting human beings against a possible influenza pandemic. Developing a truly efficient synthetic route by which Tamiflu can be produced in sufficient amounts to satisfy a worldwide demand is an ongoing project in our group.…”
Section: Catalytic Asymmetric Synthesis Of Tamiflumentioning
confidence: 99%
“…Based on the importance of the cyclopropane unit, and the pioneering investigations of Aggarwal and Gaunt, Matsunaga, Shibasaki and coworkers began to investigate the possible use of rare-earth metals for the asymmetric cyclopropanation of enones and α,β-unsaturated acylpyrroles [33]. In addition, their previous development of catalytic enantioselective epoxidation reactions of the same substrates supported the suggestion that a domino Michael/intramolecular substitution mechanism would be applicable to asymmetric reactions with stabilized ylides.…”
Section: Miscellaneousmentioning
confidence: 99%